Transformasi Pesantren di Indonesia: Peran dalam Pendidikan Islam, Nasionalisme, dan Perubahan Sosial - Shapiah, Shapiah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study examines the role of Islamic boarding schools in the development of Islamic education in Indonesia, especially in the 19th to early 20th centuries, and its impact on the national movement and social transformation. This study uses a qualitative approach with historical methods, relying on literature studies and data analysis from various secondary sources such as books, journal articles, and related documentation. The results of the study show that Islamic boarding schools as traditional Islamic educational institutions, not only function as centers of religious learning, but also as agents of social change and character formation. Through religious education that teaches moral values, ethics, and a spirit of independence, Islamic boarding schools play a strategic role in introducing nationalism and fighting colonial occupation. This study also identifies the modernization of Islamic boarding schools after independence, which integrates formal education and science with a religion-based curriculum. In addition, this study highlights the challenges and opportunities of Islamic boarding schools in the digital era and globalization, which paves the way for the development of Islamic boarding school education that is more adaptive to the needs of the times. The findings of this study indicate that Islamic boarding schools not only play a role in maintaining Islamic identity, but also in forming a society that is nationalistic, competitive, and ready to face global challenges. This research is expected to contribute to the development of Islamic education that is relevant to the social and cultural context of today's Indonesia.